Penerapan Metode Word and Phrase Level of Training Pada Kasus Dislogia dengan Kondisi Disabilitas Intelektual: Studi Kasus Tunggal - Rusdi Rasyid, Yulidar; Octriviani, Shendy; Azzahra (22020), Kaisa (Akademi Terapi Wicara, 2024)
Intellectual developmental delays, previously known as mental retardation, are brain development conditions that affect an individual's ability to think, learn, and function independently. The ability of a dyslogia child with mental retardation, currently known as intellectual disability, to name the word level of nouns can improve expressive language skills, and which are part of verbal communication.